2011
DOI: 10.1117/1.3574762
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of breast tumor phantoms containing carbon nanotubes and nanohorns

Abstract: Abstract.The degree by which optical properties of tumors are altered following introduction of carbon nanotubes (CNTs) of varying concentration and type is poorly understood, making it difficult to predict the impact of CNT inclusion on the photothermal response to laser therapies. Optical properties were measured of phantoms representative of breast tumor tissue incorporated with multiwalled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs), and single-walled carbon nanohorns (SWNHs) of varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 64 publications
(88 reference statements)
0
30
0
Order By: Relevance
“…Nanocarbons, such as carbon nanotubes (CNTs) and carbon nanohorn (CNH), are considered useful in science and technology because of their remarkable physical and chemical properties, some of which might help overcome the limitations of traditional laser light technologies. In particular, nanocarbons have extraordinary photothermal energy conversion efficiency and high absorption cross-sections in a wavelength range capable of transmission within the diagnostic window (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Although gold nanoparticles also have such photothermal properties, nanocarbons can be more effectively heated at various wavelengths because of their strong absorbance over a wide range of the optical region (38).…”
mentioning
confidence: 99%
“…Nanocarbons, such as carbon nanotubes (CNTs) and carbon nanohorn (CNH), are considered useful in science and technology because of their remarkable physical and chemical properties, some of which might help overcome the limitations of traditional laser light technologies. In particular, nanocarbons have extraordinary photothermal energy conversion efficiency and high absorption cross-sections in a wavelength range capable of transmission within the diagnostic window (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Although gold nanoparticles also have such photothermal properties, nanocarbons can be more effectively heated at various wavelengths because of their strong absorbance over a wide range of the optical region (38).…”
mentioning
confidence: 99%
“…The absorption and reduced scattering coefficients of the skin phantoms were 0.06 mm −1 (594 nm) and 0.05 mm −1 (710 nm), and 1.8 mm −1 (594 nm) and 1.5 mm −1 (710 nm), respectively, each with standard deviations varying from ±0.02–0.08. 28 …”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…We adopted the common assumption that a soft turbid tissue behaves as an isotropic medium, when the scattering is expressed in terms of a reduced scattering coefficient. 24, 28 The source in Equation 1 is a Gaussian beam in the vicinity of the laser focus constructed from Beer’s law as an isotropic scattering event (Equations 2 and 3). Sex=μS'·false(1Rspfalse)·ϕex0·normalexpfalse(μt·zfalse) ϕex0=Iexamp·efalse(x22σx2+y22σy2false) In these equations, R sp denotes the specular reflectance from the surface of the scattering medium, Φ ex0 denotes the incident fluence on the surface, µ t represents the attenuation coefficients (µ t = µ aex +µ´ s ), I amp ex is the amplitude of the Gaussian laser spot, and σ defines the excitation area dimensions.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the C sca /C abs ratio of gold nanospheres with radius of 10 nm under 521 nm light is only 0.01 [23]. A recent study showed that scattering from larger diameter multiple walled carbon nanotubes (MWCNTs) is minor (<8%) in light extinction over the wavelength range of 300-1300 nm [24]. Thus, it is reasonable to hypothesize that absorption spectroscopy may be an effective tool to measure the length of SWCNTs.…”
Section: Introductionmentioning
confidence: 99%